Analysis of the prospects of phase change materials in building structures - A. V. Fedyukhin; O. V. Afanaseva; M. D. Zaitsev (Vestnik MGSU)
Introduction. The objective of the study is to analyze the prospects of application of phase change materials in building structures. The relevance of the work is due to the industry trend to reduce the consumption of heat energy by buildings through the use of modern thermal insulation materials and enclosing structures. Phase change materials produced in industrial volumes and used in construction in foreign countries are chosen as the object of research. The ability of these materials to absorb and release heat energy can be used to improve the thermal characteristics of buildings. Analysis of the possibility of using these materials in building structures was carried out for three cities of the Russian Federation: Moscow, St. Petersburg and Sochi.Materials and methods. The efficiency of the use of phase change materials in building structures was carried out by means of energy modelling of the building using the Conduction Finite Difference algorithm in the EnergyPlus programme, taking into account climatic conditions and energy consumption for heating and cooling of the building. The calculation was performed for structures including phase change materials (3 different materials with phase change), and without them.Results. The values of energy consumption for space heating and cooling, absolute and relative energy savings from the use of phase change materials were determined.Conclusions. The analysis showed that the energy and economic effect from the application of materials with phase change in building structures is from 2 to 13 % and depends on both the type of material and the region of application.